A voz decolonial do Rap nacional - Moraes, Flavio Henrique (2021)
In each social sphere, some types of statements are predominant, and it is through them that the understanding of oneself and the other is established. Since all West ern civilization is determined by everything that was configured from the idea and enterprise that was conventionally called the West and that, in turn, was the result of constant processes of colonization and coloniality of peoples, biomes, cultures, that is, of countless forms of life as we know them today, all of our subjectivity and objectivity are mediated and validated by Western, Eurocentric epistemology, start ing with the linguistic expression we express ourselves.Basically, the West was based on actions of colonization and coloniality that are based on the idea of race, gender and class, which justified massacres and the process of elimination still un derway. Apart from the ideal configuration of a Eurocentric model of civilization, a powerful statement that emerged in the 1960s in Brooklyn, rap, in the midst of the Hip Hop Movement, disputes and exposes the wounds of these colonialities that constantly produce deaths and wars. The thesis presented here will seek to show how the rap statements opened up and denounced processes of coloniality that are still ongoing, however they can and must be overcome through decolonial and dia logical orientations, which value alterity and dialogue. The thinkers who help us in this research are: Walter Mignolo, Mikhail Bakhtin, Quijano, Catherina Walsh, Fanon and others from areas that consider the need for disobedience or epistemic recon siderations